2015
DOI: 10.1371/journal.pone.0132183
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Suitable Reference Genes for Quantitative Real-Time PCR in Heterosigma akashiwo (Raphidophyceae)

Abstract: The raphidophyte Heterosigma akashiwo is a globally distributed harmful alga that has been associated with fish kills in coastal waters. To understand the mechanisms of H. akashiwo bloom formation, gene expression analysis is often required. To accurately characterize the expression levels of a gene of interest, proper reference genes are essential. In this study, we assessed ten of the previously reported algal candidate genes (rpL17-2, rpL23, cox2, cal, tua, tub, ef1, 18S, gapdh, and mdh) for their suitabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 55 publications
(62 reference statements)
2
18
0
Order By: Relevance
“…To examine the effects of low levels of N or P on gene expression in H . akashiwo cultures were treated as previously described (Ji et al ., ), with low N (181.5 μM NaNO 3 and 36.3 μM NaH 2 PO 4 , 5:1 of N:P), low P (883 μM NaNO 3 and 7.06 μM NaH 2 PO 4 , 125:1 of N:P), and nutrient replete ( f /2 medium). Each culture condition was set up in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…To examine the effects of low levels of N or P on gene expression in H . akashiwo cultures were treated as previously described (Ji et al ., ), with low N (181.5 μM NaNO 3 and 36.3 μM NaH 2 PO 4 , 5:1 of N:P), low P (883 μM NaNO 3 and 7.06 μM NaH 2 PO 4 , 125:1 of N:P), and nutrient replete ( f /2 medium). Each culture condition was set up in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, commonly used ICGs can considerably vary between species, tissue types and experimental conditions (Li and Shen, 2013). Furthermore, the conventional use of a single ICG to normalize the target mRNA transcripts may produce unreliable data (Ji et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA from the samples was extracted using the TRIreagent (Molecular Research Center, USA), and purified using Direct-zol RNA Miniprep (Zymo research, USA), as previously reported (Ji et al, 2015). The RNA concentration and quality was determined using NanoDrop spectrophotometer (Thermo, Germany).…”
Section: Total Rna Extraction and Cdna Synthesismentioning
confidence: 99%
“…To examine the specificity of each primer, regular PCR were performed and the size of PCR products were examined on agarose gel, and the products were cloned and sequenced. In addition, the PCR amplification efficiency (E) of each primer set was analyzed following E = [10 (À1/slope) ] Â 100% (Supplementary Table S2), in which the slope were obtained from the standard curve generated from a serial dilutions of a pooled cDNA sample, as previously described (Bustin et al, 2009;Coyne et al, 2005;Ji et al, 2015).…”
Section: Quantitative Reverse-transcription Pcr (Qrt-pcr)mentioning
confidence: 99%
See 1 more Smart Citation